PENERAPAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS GAMBAR DALAM MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN PADA SISWA KELAS I DI SD PALM KIDS PALEMBANG - Andini Rahmadani; Alsyah Syafira Rahmadani; Siti Annisa; Dinda Putri Siwanda; Azzahra Putri Lauza (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to describe the application of picture-based Student Worksheets (LKPD) in improving students’ understanding of multiplication concepts in Grade I at SD Palm Kids Palembang. The problem found during the School Field Introduction Program (PLP) showed that several students still had difficulty understanding multiplication as repeated addition. Students tended to memorize multiplication results without fully understanding the relationship between the number of groups and the number of objects in each group. This study used a descriptive qualitative method based on observation, teaching assistance, independent teaching practice, and documentation. The subjects were 24 students of Grade I Independent, consisting of 13 male students and 11 female students. The implementation of picture-based LKPD used visual objects such as candies, cakes, fruits, and marbles to help students understand multiplication in a concrete way. The results showed that picture-based LKPD made students more active, enthusiastic, and confident in learning mathematics. Students were also able to identify groups of objects, count repeated additions, and write simple multiplication sentences more easily. Therefore, picture-based LKPD can be used as an effective and interesting learning medium to improve students’ understanding of multiplication concepts in lower elementary school grades.